Research progress in unilateral moyamoya disease - Xiaokuan Hao; Cunxin Tan; Ziqi Liu; Yang Tie; Yanru Wang; Shihao He; Ran Duan; Rong Wang; Rong Wang (Frontiers in Human Neuroscience)
Unilateral moyamoya disease (U-MMD) is a chronic vascular disease characterized by progressive stenosis and occlusion of the terminal end of the internal carotid artery and its main branches, resulting in the appearance of moyamoya-like blood vessels at the base of the brain. The etiology of U-MMD is unknown, it accounts for 9.7–17.8% of all moyamoya disease, and the family incidence is 5.5–13.3%. The clinical characteristics are similar to those of typical moyamoya disease, but there are some differences. U-MMD can progress to bilateral moyamoya disease with a median probability of 29.01% (ranging from 6.3 to 58.8%), and there are many risk factors that promote its development. Surgical treatment can effectively reduce the incidence of ischemic stroke and improve prognosis. However, the timing and indications for surgery require further investigation. This article reviews the latest research progress on the etiology, epidemiology, clinical and radiological characteristics, progression, treatment, and prognosis of U-MMD.